Simulações de daltonismo no desenvolvimento de jogos cromaticamente acessíveis para dispositivos móveis - Carneiro, Mateus Pinheiro de Góes (2024)
Video games are an important part of modern culture, particularly after the popularization of mobile devices, and should, therefore, be accessible to all people. However, even with the advancement of mobile accessibility, players with visual disabilities still face barriers due to the inherent focus of games on visual stimuli. In this context, color blind players are affected by how colors are used in the interfaces, especially when these colors are the basis for essential game mechanics. However, creating chromatically accessible games imposes some challenging aspects such as the limited availability of color-blind participants for testing and the importance of identifying and considering accessibility threats even in the early stages of development. In this context, this work explores the use of these tools in the development of games for mobile devices. For this, a 5-step methodology was used, including 3 experiments that sought to (1) explore the use of different types of color blindness simulation in the real context of developing a mobile game, (2) verify the use color blindness simulations to identify color accessibility problems in games and (3) analyze the perception of color meanings in games through color blindness simulations. Results point to advantages in the use of these tools in different stages of game development when combined with accessibility guidelines and tests with color blind players. In addition, the issues raised by this work were organized into recommendations to help game designers and developers to integrate color blindness simulations into their professional activity.